Turing instability mechanism of short-memory formation in multilayer FitzHugh-Nagumo network - Wang, Junjie; Shen, Jianwei (Frontiers in Psychiatry, 2023)
The study of brain function has been favored by scientists, but the mechanism of short-term memory formation has not been precise. Since the formation of short-term memories depends on activity in populations of neurons, we try to explain the formation principle of short-term memory from the neuron level in this paper. Due to the modular structures of the brain, we analyze the pattern properties of the Fitzhugh-Nagumo model (FHN) on multilayer network (coupled by random network). The conditions of Turing instability are obtained by comparison principles. It is found that the change in diffusion coefficients and network connection probability will affect the formation of short-term memory. Then the time delay is introduced to more closely match patterns of brain activity. The properties of periodic solutions are obtained. It is found that the network affects the value of. And it is found that network and time delay can induce complex cluster dynamics and the synchrony increases with the increase of p, which plays a crucial role in forming short-term memory.